SLC9A3 Protein Is Critical for Acrosomal Formation in Postmeiotic Male Germ Cells - Wang, Ya-Yun (Int J Mol Sci, 2017)
Solute carrier family 9 isoform 3 (SLC9A3), a Na(+)/H(+) exchanger, regulates the transepithelial absorption of Na(+) and water and is primarily expressed on the apical membranes of the intestinal epithelium, renal proximal tubule, epididymis, and vas deferens. Loss of the Slc9a3 allele in mice enhances intestinal fluid and causes diarrhoea as a consequence of diminished Na(+) and HCO(3)(−) absorption. Hence, the loss also causes male infertility and reveals the abnormal dilated lumen of the rete testis and calcification in efferent ductules. However, whether loss of Slc9a3 alleles also disrupts mammalian spermatogenesis remains unknown. First, through immunoblotting, we determined that SLC9A3 is highly expressed in the murine testis compared with the small intestine, epididymis, and vas deferens. During murine spermatogenesis, SLC9A3 is specifically expressed in the acrosome region of round, elongating, and elongated spermatids through immunostaining. Furthermore, SLC9A3 signals are enriched in the acrosome of mature sperm isolated from the vas deferens. In Slc9a3 knockout (KO) mice, compared with the same-aged controls, the number of spermatids on the testicular section of the mice progressively worsened in mice aged 20, 35, and 60 days. Sperm isolated from the epididymis of Slc9a3 KO mice revealed severe acrosomal defects. Our data indicated that SLC9A3 has a vital role in acrosomal formation during spermiogenesis.